2020
DOI: 10.1007/s00396-020-04742-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of arm composition on the self-assembly of low-functionality telechelic star polymers in dilute solutions

Abstract: We combine synthesis, physical experiments, and computer simulations to investigate self-assembly patterns of low-functionality telechelic star polymers (TSPs) in dilute solutions. In particular, in this work, we focus on the effect of the arm composition and length on the static and dynamic properties of TSPs, whose terminal blocks are subject to worsening solvent quality upon reducing the temperature. We find two populations, single stars and clusters, that emerge upon worsening the solvent quality of the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…26 In this work we explore, by means of full-monomer numerical simulations, the properties of diblock copolymer brushes grafted to a spherical colloidalso referred to as diblock copolymer star (DCS) brush. Diblock copolymer brushes composed of polybutadine-polysterene have been recently synthesized using state-of-the-art techniques, 27,28 and the accompanying numerical simulations have shown that the simple modeling we put forward here is capable of capturing the salient characteristics under both dilute and semidilute conditions. First, we consider a DCS brush in the bulk and show that, as the solvophobic sections of the brush aggregate, we can identify patches as clusters of monomers belonging to different arms, as prescribed in the literature; 23 DCS brushes thus constitute examples of soft patchy particles.…”
Section: Introductionmentioning
confidence: 99%
“…26 In this work we explore, by means of full-monomer numerical simulations, the properties of diblock copolymer brushes grafted to a spherical colloidalso referred to as diblock copolymer star (DCS) brush. Diblock copolymer brushes composed of polybutadine-polysterene have been recently synthesized using state-of-the-art techniques, 27,28 and the accompanying numerical simulations have shown that the simple modeling we put forward here is capable of capturing the salient characteristics under both dilute and semidilute conditions. First, we consider a DCS brush in the bulk and show that, as the solvophobic sections of the brush aggregate, we can identify patches as clusters of monomers belonging to different arms, as prescribed in the literature; 23 DCS brushes thus constitute examples of soft patchy particles.…”
Section: Introductionmentioning
confidence: 99%
“…The central message from the rheological and SAXS studies is the unambiguous tunability of the dynamic response of micelles and TSPs as the temperature is reduced from the amorphous liquid regime. However, the formed ordered phases in the intermediate-temperature and the low-temperature re-entrant regimes are not as coherent and unambiguous as in other block copolymer cylindrical phases …”
Section: Resultsmentioning
confidence: 82%
“…Finally, note that the model employed is not a result of systematic coarse-graining that would retain the details of microscopic interactions necessary for a quantitative comparison against the experiments. Rather, it aims at rationalizing generic trends in system assembly as a function of the main control parameters. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…Moghimi et al 192 combined synthesis, experiments and computer simulations to investigate self‐assembly patterns of low‐functionality telechelic star polymers (TSPs) in dilute solutions as a function of temperature and solvent quality, the main focus being the effect of the arm composition and length. Zhang et al 193 compared the self‐assembly and pH/oxidation responsivity of a linear and cyclic toothbrush copolymer.…”
Section: Study‐through‐synthesis Approach In Msr Copolymersmentioning
confidence: 99%